2017
DOI: 10.1007/s10806-017-9664-9
|View full text |Cite
|
Sign up to set email alerts
|

Time for a New EU Regulatory Framework for GM Crops?

Abstract: In recent years, the EU legislation on genetically modified (GM) crops has come under severe criticism. Among the arguments are that the present legislation is inconsistent, disproportionate, obsolete from a scientific point of view, and vague in terms of its scope. In this paper, the EU GM legislation (mainly the ''Release Directive'', 2001/18/EC) is analysed based on five proposed criteria: legal certainty, non-discrimination, proportionality, scientific adaptability, and inclusion of non-safety consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Models for setting up different risk-based categories of organisms and/or techniques have already been developed (Barton et al, 1997 ; Miller, 2010 ; Beker et al, 2016 ; Conko et al, 2016 ; Ricroch et al, 2016 ), whereas the EU is currently in practice arguably very far away from living up to these original intentions. Zetterberg and Edvardsson Björnberg ( 2017 ) have also recently suggested that a new protocol for risk assessment incorporating selected aspects of traits and gene functions, rather than the mere presence of recombinant nucleic acids in the product, may contribute to making the EU GMO legislation more consistent regarding criteria such as non-discrimination of techniques and scientific adaptability taking the latest scientific findings into account. In this context, it is also worth noting that the Norwegian Biotechnology Advisory Board has initiated a public discussion on the future regulation of gene technologies, asking if there is a need for new dividing lines (Norwegian Biotechnology Advisory Board, 2018 ).…”
Section: Early Drafting Of the Gmo Regulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Models for setting up different risk-based categories of organisms and/or techniques have already been developed (Barton et al, 1997 ; Miller, 2010 ; Beker et al, 2016 ; Conko et al, 2016 ; Ricroch et al, 2016 ), whereas the EU is currently in practice arguably very far away from living up to these original intentions. Zetterberg and Edvardsson Björnberg ( 2017 ) have also recently suggested that a new protocol for risk assessment incorporating selected aspects of traits and gene functions, rather than the mere presence of recombinant nucleic acids in the product, may contribute to making the EU GMO legislation more consistent regarding criteria such as non-discrimination of techniques and scientific adaptability taking the latest scientific findings into account. In this context, it is also worth noting that the Norwegian Biotechnology Advisory Board has initiated a public discussion on the future regulation of gene technologies, asking if there is a need for new dividing lines (Norwegian Biotechnology Advisory Board, 2018 ).…”
Section: Early Drafting Of the Gmo Regulationsmentioning
confidence: 99%
“…In light of the overwhelming evidence of benefits demonstrated by the references listed above as well as the absence of associated risks, it can be argued that certain applications of GMOs and/or their derived products are compatible with an interpretation of the precautionary principle that would promote, rather than prohibit, these applications. Returning to the analysis by Zetterberg and Edvardsson Björnberg ( 2017 ), they also suggest an alternative regulatory model based on sustainability criteria that apply to all varieties regardless of the applied breeding methods. This model would certainly be compatible with the precautionary principle as the primary goal would not be to merely avoid risk by refraining from the use of certain techniques but instead to achieve a broader set of sustainability goals.…”
Section: Early Drafting Of the Gmo Regulationsmentioning
confidence: 99%
“…The proposal of integrating value considerations into the admission process of genome editing and its agricultural products will face a number of problems. A classical objection is that value criteria are vague and subjective (Zetterberg and Björnberg, 2017 ) and therefore not easy to justify. Value-sensitive regulations must also be defended against the reproach of nudging the public in a paternalistic way when they are state-imposed.…”
Section: Food Labeling As An Institution For Value Deliberations Concmentioning
confidence: 99%
“…This article will discuss arguments concerning the inclusion of what Zetterberg and Björnberg ( 2017 ) have called ‘non-safety’ criteria in the regulation of genome-edited organisms, and explore under which circumstances assessment according to these criteria should be required in order to ensure that use of genome-edited organism are ethically justifiable and socially acceptable. Non-safety assessments are required for GMOs in some countries, such as Norway, where they are an addition to the compulsory risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…While Zetterberg and Björnberg ( 2017 ) focuses on the European Union (EU) regulatory framework for GMOs, this article will present the Norwegian Act and its system for assessment of sustainability, societal utility and ethics. This includes an overview of the current regulatory practice in Norway under the GTA, explicating normative bases for decisions in actual cases, and a discussion of whether it is possible to operationalize non-safety assessments, determining the feasibility of such assessments.…”
Section: Introductionmentioning
confidence: 99%